Force-velocity, impulse-momentum relationships: Implications for efficacy of purposefully slow resistance training - Schilling, B. K.; Falvo, M. J.; Chiu, L. Z. F. (Journal of Sports Science & Medicine, 2008)
The purpose of this brief review is to explain the mechanical relationship between impulse and momentum when resistance exercise is performed in a purposefully slow manner (PS). PS is recognized by ~10s concentric and ~4-10s eccentric actions. While several papers have reviewed the effects of PS, none has yet explained such resistance training in the context of the impulse-momentum relationship. A case study of normal versus PS back squats was also performed. An 85kg man performed both normal speed (3 sec eccentric action and maximal acceleration concentric action) and PS back squats over a several loads. Normal speed back squats produced both greater peak and mean propulsive forces than PS action when measured across all loads. However, TUT was greatly increased in the PS condition, with values fourfold greater than maximal acceleration repetitions. The data and explanation herein point to superior forces produced by the neuromuscular system via traditional speed training indicating a superior modality for inducing neuromuscular adaptation.